THE EFFECT OF YOUTUBE VIDEO ON IMPROVING MATHEMATIC COMMUNICATION SKILLS OF THE STUDENTS OF PRIMARY SCHOOL TEACHER EDUCATION - Siti Ruqoyyah; Hana Sakura Putu Arga; Medita Ayu Wulandari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study was motivated by the low mathematical communication skills of students of prospective primary school teacher. The purpose of this study was to see and to improve the mathematical communication skills of the students of prospective primary school teachers through YouTube videos. This study utilized a quasi-experimental method with a non- equivalent pretest and posttest control group design. The population were all students of the second semester students of primary school teacher candidates in Cimahi, West Java, Indonesia. Meanwhile, the samples in this study were 60 second semester students at one of private universities in Cimahi. The instrument in this study was a test to measure mathematical communication skills. The results showed that 1) The achievement and improvement of the mathematical communication skills of the students of prospective primary school teachers who used YouTube videos were better than students who used conventional learning; and 2) Learning mathematics using YouTube videos made students accustomed to communicating all of their mathematical ideas and students became more confident, active, and creative.